Análise das características químicas, físico-químicas, bacteriológicas e sanitárias da água usada para consumo humano nas comunidades Indígenas Maxakali da região nordeste de Minas Gerais/Brasil - Assis, Eliseu Miranda de (Universidade do Vale do Rio dos Sinos, 2016)
The colonization process led to the extinction of many indigenous societies that lived in the dominated territory, whether through the action of weapons, enslavement of indigenous people, contagion by diseases brought from distant countries, or even through the application of policies aimed at the "integration" of the Indians to the new dominant society, with strong European influence. Data from the Indigenous Health Care Information System (SIASI, 2008) shows that in the Maxakalí population from 2000 to 2007, parasitic and infectious diseases represented the main cause of death (20.57%), with a risk of 3.18 for every 100 Maxakalí Indians. The absence of sanitary conditions, such as the inexistence of an infrastructure for the adequate disposal of waste and access to good quality water, demonstrate a scarcity or poor administration of public resources for the country's indigenous populations. In this context, when contaminated water can transmit pathogenic agents of bacterial diseases such as typhoid fever, paratyphoid fever, bacillary dysentery, enteroinfections in general and cholera, in addition to viral diseases such as infectious hepatitis and poliomyelitis. Thus, testing the water quality parameters and verifying that they are within the limits established for risk-free consumption, within the standards established by CONAMA (1986), represents both a service for these communities and a survey of a body of relevant data and necessary for research to characterize these locations from a social and environmental point of view.
Keywords: Qualidade da água; Populações indígenas; Water quality; Indigenous populations; ACCNPQ::Ciências da Saúde::Saúde Coletiva